2-Simple ore domains of stable rank 1 - Domsha, O.V.; Zabavskii, B. V. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
It is known that a simple Bézout domain is a domain of elementary divisors if and only if it is 2-simple. We prove that, over a 2-simple Ore domain of stable rank 1, an arbitrary matrix that is not a divisor of zero is equivalent to a canonical diagonal matrix.